User resistance and repurposing: a look at the iOS jailbreaking scene in Brazil - Amaral, Adriana da Rosa; Souza, Rosana Vieira (AoIR Selected Papers of Internet Research, 2013)
The paper aimed to discuss the growth of mobile platforms and the emergence of the user counter-power in these environments. In that respect, we intended to reflect upon jailbreaking practices from the users’ point of view. The study is based on a qualitative approach that examined critical incidents and included interviews with Cydia Store users from Brazil, the primary jailbreak apps store available to users of iOS devices. We discuss how the users of jailbroken handsets articulate the tensions between jailbreaking practice and market constraints, as well as the trade-offs and paradoxes (e.g. security versus openness, stability versus freedom) the users have to deal with in the jailbreaking scene. Our findings suggest that even though jailbreaking practices reflect social counter-power, it emerges from a free culture logic that legitimates the freedom to access, distribute or modify content and creative work, and not from an explicit political motivation.